Chokepoint capitalism : how big tech and big content captured creative labor markets and how we'll win them back - Giblin, Rebecca; Doctorow, Cory (Boston: Beacon Press, 2022)
"People are feeling squeezed because of chokepoint capitalism: exploitative businesses creating barriers to competition that let them take over markets and extract an unfair share of value. This book teaches how to spot those chokepoints, and what we can do to blow them up"-- "People are feeling squeezed because of chokepoint capitalism: exploitative businesses creating barriers to competition that let them take over markets and extract an unfair share of value. This book teaches how to spot those chokepoints, and what we can do to blow them up"--